Living with Omega-3: New Materialism and Enduring Concerns. (February 2015) - Abrahamsson, Sebastian; Bertoni, Filippo; Mol, Annemarie; Martín, Rebeca Ibáñez
In the early 21st century quite a few social scientists and scholars in the humanities are arguing that we should pay more attention to things material. For, as they say, not only humans act but so, too, do materials. Joining this discussion, in this paper we will use the case of omega-3 fatty acids to address the questions of how materials may act; in which ways this is relevant; and what is linked up with it. Hence, we will come to speak about research in prisons where inmates were badly nourished; fish being caught in the Global South for Scandinavian fish pills; and the urgency of shifting from the verb 'to act' to a differentiated list of modes of doing. Learning from the natural sciences, we will argue, requires that their methods and concerns be carefully attended to. Taking matters seriously comes with the obligation of tracing where such matters come from and where they go. And talking about 'action', finally, demands that, beyond liberal notions of isolated individual actors, it be creatively retheorised.